Stock Index, Interest Rate and Gold Price of Nepal: Cointegration and Causality Analysis - Gaire, Hom Nath (NRB Economic Review, 2017)
This study examines cointegration and causality between the NEPSE index vis-à-vis short term interest rates and gold prices in Nepal. Main objective of this study is to identify the long run equilibrium relationship as well as cause and effect relationship between the variables under consideration. Monthly time series data cover the period starting from January 2006 to December 2016, which were sourced from Nepal Stock Exchange (NEPSE), Nepal Rastra Bank (NRB) and Nepal Gold and Silver Dealers Association (NEGOSIDA). The results of the unit root (ADF) tests and Cointegration (Johansen) tests confirm that there is long-run equilibrium relationship between the NEPSE index, short term interest rates and gold prices in Nepal. In the meantime, Granger Causality test reveals that there is no causality between the gold price and NEPSE index. However, it is confirmed that there is unilateral causal relationship between the NEPSE index and short term interest rate which moves from interest rate to NEPSE index. From the test results it can be concluded that the short-term interest rates are the better predictor for NEPSE index and bullion (commodity) market is yet to be developed as substitute of the Stock Market.